2022
DOI: 10.3390/ijerph19063659
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Wellbeing during the COVID-19 Pandemic: A Mixed-Methods Exploration of Frontline Homelessness Services Staff Experiences in Scotland

Abstract: Staff working in homelessness services often find the work rewarding yet challenging, and the sector experiences high levels of staff burnout and staff turnover. During the COVID-19 pandemic, staff working in these services faced particularly stressful working conditions. This study explored the experiences of stress and wellbeing among those working in frontline homelessness service roles during the early stages of the pandemic in Scotland. Semi-structured interviews were conducted with 18 participants, 11 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In line with wider research on health-care workers (Korunka et al , 2009), staff simultaneously report being exhausted, yet absorbed and motivated towards their work. Carver and colleagues (2022) identified that homelessness staff working through the COVID-19 pandemic reported being both exhausted, yet emotionally identifying with their work; when staff are faced with constrained resources and a complex system, their empathy and engagement with their work can act as a stressor in and of itself. Staff in homelessness services are more likely to experience anxiety and depression compared to the general population (Lemieux‐Cumberlege and Taylor, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In line with wider research on health-care workers (Korunka et al , 2009), staff simultaneously report being exhausted, yet absorbed and motivated towards their work. Carver and colleagues (2022) identified that homelessness staff working through the COVID-19 pandemic reported being both exhausted, yet emotionally identifying with their work; when staff are faced with constrained resources and a complex system, their empathy and engagement with their work can act as a stressor in and of itself. Staff in homelessness services are more likely to experience anxiety and depression compared to the general population (Lemieux‐Cumberlege and Taylor, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they experience high levels of exposure to stressful and traumatic events in workplaces that do not always provide critical incident training (Ceannt et al, 2016), despite the documented benefits of providing such training (Hopper et al, 2010;Levesque et al, 2021). Negative repercussions of these impacts on staff often include high rates of sick leave and stress leave; the consequent lack of adequate staffing can result in the delivery of substandard or poor services (Campbell et al, 2022;Carver et al, 2022). This, in turn, negatively affects people experiencing homelessness and may lead to disengagement with homeless services, and prolonged homelessness (Kerman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic may have exacerbated the mental health challenges faced by staff, creating additional challenges for homelessness-serving organizations (Carver et al, 2022). However, little is known about how intersectional factors such as gender and ethnicity, which have their own work-related stressors, create an additional impact on staff who belong to marginalized and racialized groups.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in a US study of emergency shelter providers in Texas, most were worried about being exposed to and contracting COVID‐19 at work, which had a negative impact on burnout levels (Aykanian, 2022 ). Factors that may have exacerbated the stress levels of service providers during the pandemic included changes to how supports were delivered, increased demand for services due to closure of other programmes, and a heightened need to effectively balance risks and benefits in work‐related decisions (Carver et al, 2022 ; Kaur et al, 2022 ; Parkes et al, 2021 ; Pixley et al, 2022 ). Yet, as organisations serving individuals experiencing homelessness were forced to adapt to the pandemic, this also yielded workplace innovations that had benefits for providers.…”
Section: Introductionmentioning
confidence: 99%